Etiopathological factors in reflux gastritis - Patiño, Tydeo; Trujillo, Raquel; Dinello, Sergio; Piazze, Alvaro; Fernández, Ricardo; Giossa, Walter; Bonaba, Roberto (Cirugía del Uruguay, 1987)
The authors study the effect of the pathological reflux of pure bile and of bile associated with pancreatic and duodenal liquid on gastric mucosa (preservad and suppressed vagal innervation) of dogs with different assemblies.